Isolating coccoliths from sediment for geochemical analysis - Halloran, P; Rust, N; Rickaby, R (2009)
Trace element analysis of open-marine sedimentary carbonates provides a wealth of paleoclimate data. At present, the majority of this data is obtained from foraminifera tests. Complications regarding the variability of conditions experienced by foraminifera throughout test formation and the influence of diagenetic processes on sample chemistry limit the value of foraminifera samples in certain situations. Coccoliths, the calcium carbonate plates produced by coccolithophores, represent a second major pelagic open-marine carbonate source with the potential to provide a wide range of valuable trace element proxy data but which have, until now, been unavailable for analysis of many trace elements because of clay contamination. Here we describe a novel technique, which utilizes fast sorting flow cytometry, to enable the production of clay-free sedimentary coccolith samples. © 2009 by the American Geophysical Union.